UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PERPAJAKAN MAHAISSWA DENGAN MENGGUNAKAN STRTAGEI PEMBELAJARAN MODEL KOOPERATIF GRUP INVESTIGATION - Dearlina Sinaga; Surya Darma Pardede (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
This study aims at improving the activities and learning outcomes of student taxation by applying the learning strategy of the Investigation Group (IG).This type of research is classroom action research (CAR) which has been carried out in two cycles.The research strategy used is the learning structure of the Investigation Group (IG) with the research design of the Two Groups; Pre-test and post-test design.The results of observations that have been conducted show that student learning activities were improved, namely cycle I there were 5 students or 20.84% ​​for active and very active criteria while in the second cycle of meeting I there are 14 students or as many as 58.33% for active and very active criteria, then on cycle IIon meeting II, there are 17 students or as many as 70.83% for active and very active criteria. This shows an increase in student activity from the first and second cycle. Whereas the results of student learning tests that were carried out obtained data on the average value of learning outcomes in the pre-test with an average score of 49.16 or as many as 16.66%. In the post-test cycle I the researchers applied the learning structure the Investigation Group (IG), there was an increase in scores with an average of 67.08 or as many as 62.5% of the total population while the average value in the second cycle increased to 74.16 or as many as 79.165%. Based on the results of the above research it can be concluded that applying the learning strategy the Investigation Group (IG) can improve student activities and learning outcomes.